A multi-function textile with pH-induced switch wettability transition for controllable oil−water separation. Issue 9 (May 2022) - Feng, Long; Hou, Yimiao; Hao, Qingqing; Chen, Mingxing; Wang, Shuo; Hu, Xuemin; Yang, Wenxiu
The deterioration of water ecology caused by the discharge of oil spill wastewater, industrial sewage, and municipal sewage has attracted wide attention worldwide. Thus, it is significant to design a simple, environmentally friendly approach to separate oil–water mixtures. In this work, three different fabrics with pH-induced wettability transition were prepared by a dip-coating process for oil and water separation. The dip-coating fabrics had the advantages of oil–water separation, photocatalytic degradation, and recycling. Polyethylene terephthalate/polyamide nonwoven fabric was used as the substrate materials of the fabric. The carboxylic acid-modified TiO2 endowed the fabric with hydrophilicity–hydrophobicity and photocatalytic properties. The Fe3 O4 nanoparticles obtained by the coprecipitation method provided magnetism for the fabric, facilitating the recycling of the fabric and improving the hydrophobicity of the fabric. The fabrics coated with dipping solutions were superhydrophobic in a neutral environment and hydrophilic in an alkaline environment. Among the three coated fabrics, the fabric coated with stearic acid/TiO2 -Fe3 O4 (FST) had the most satisfying oil–water separation performance and durability. Under the neutral condition, the contact angle of the FST was 151° and the separation efficiency was 98%. Under the alkaline condition, the underwater oil contact angle of the FST was 150° and the separation efficiency was 95%. After 15 cycles, the oil–water separation rate of the FST was still higher than 90%. Due to the presence of TiO2, the coated fabric had an exceptional performance in the photodegradation of organic pollutants (69.9%). In addition, the fabrics can be quickly recovered due to magnetism.